IL-17 production by CSF lymphocytes as a biomarker for cerebral vasculitis. Issue 2 (April 2016) - Thom, Vivien; Schmid, Sabrina; Gelderblom, Mathias; Hackbusch, Romy; Kolster, Manuela; Schuster, Simon; Thomalla, Götz; Keminer, Oliver; Pleß, Ole; Bernreuther, Christian; Glatzel, Markus; Wegscheider, Karl; et al.
Abstract : Objective: To explore the possibility of using interleukin-17 (IL-17) production by CD4+ T cells in the CSF as a potential biomarker for cerebral vasculitis in stroke patients. Methods: In this consecutive case study, we performed prospective analysis of CSF and blood in patients admitted to a university medical center with symptoms of stroke and suspected cerebral vasculitis. Flow cytometry was performed for intracellular detection of inflammatory cytokines in peripheral blood lymphocytes and expanded T cells from CSF. Results: CSF CD4+ lymphocytes from patients with cerebral vasculitis showed significantly higher levels of the proinflammatory cytokine IL-17 compared to patients with stroke not due to vasculitis or with other, noninflammatory neurologic diseases. There was no difference in the production of interferon-γ in the CSF and no overall differences in the relative frequencies of peripheral immune cells. Conclusions: Intracellular IL-17 in CSF cells is potentially useful in discriminating cerebral vasculitis as a rare cause in patients presenting with ischemic stroke. Classification of evidence: This study provides Class II evidence that an increased proportion of IL-17-producing CD4+ cells in CSF of patients presenting with stroke symptoms is indicative of cerebral vasculitis (sensitivity 73%, 95% confidence interval [CI] 39–94%; specificity 100%, 95% CI 74%–100%).